2018
DOI: 10.4110/in.2018.18.e5
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific Role of CX3CR1 Expressing Immune Cells and Their Relationships with Human Disease

Abstract: Chemokine (C-X3-C motif) ligand 1 (CX3CL1, also known as fractalkine) and its receptor chemokine (C-X3-C motif) receptor 1 (CX3CR1) are widely expressed in immune cells and non-immune cells throughout organisms. However, their expression is mostly cell type-specific in each tissue. CX3CR1 expression can be found in monocytes, macrophages, dendritic cells, T cells, and natural killer (NK) cells. Interaction between CX3CL1 and CX3CR1 can mediate chemotaxis of immune cells according to concentration gradient of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
119
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(131 citation statements)
references
References 102 publications
2
119
0
Order By: Relevance
“…We have also shown that SDP stimulates the expression of F4/80 and CX3CR1, which are macrophage markers in the gut with important roles in the priming of immune responses. CX3CR1+ macrophages produce immunoregulatory cytokines such as IL-10 and can also facilitate the differentiation and maintenance of Treg within the lamina propria 56 . They are also required for the induction of the efferent CD8+ reg-T cells required for peripheral tolerance 57 .…”
Section: Discussionmentioning
confidence: 99%
“…We have also shown that SDP stimulates the expression of F4/80 and CX3CR1, which are macrophage markers in the gut with important roles in the priming of immune responses. CX3CR1+ macrophages produce immunoregulatory cytokines such as IL-10 and can also facilitate the differentiation and maintenance of Treg within the lamina propria 56 . They are also required for the induction of the efferent CD8+ reg-T cells required for peripheral tolerance 57 .…”
Section: Discussionmentioning
confidence: 99%
“…The idea that uric acid might act as a direct proinflammatory stimulus for human macrophages is also supported by two additional facts: (a) the expression pattern of CX3CR1 and CCR2 and (b) the phagocytic activity of macrophages. CX3CR1 and CCR2 are both involved in mediating monocyte recruitment to the inflammation sites, where these cells will differentiate into macrophages and orchestrate inflammatory responses or tissue repair [42,43]. Interestingly, numerous studies have consistently reported the downregulation of CX3CR1 and CCR2 in the presence of prototypical inflammatory stimuli, such as LPS.…”
Section: Discussionmentioning
confidence: 99%
“…We also compared the expression of CX3CR1, NKp46, and NKp44 on NK cells between CD patients and healthy controls. CXC3R1 is a C-X3-C-type chemokine receptor that binds to CXC3L1/fractalkine and is implicated in the chemotaxis of immune cells to sites of inflammation in the body [36]. NKp46 and NKp44 are activating receptors belonging to the Natural Cytotoxicity Receptor (NCR) family [3].…”
Section: Expression Of Integrins On Nk Cellsmentioning
confidence: 99%